Nopol production over Sn-MCM-41 synthesized by different procedures – Solvent effects (2010)
ABSTRACT: Nopol production over impregnated Sn-MCM-41 under several reaction conditions was examined and compared with Sn-MCM-41 materials previously synthesized by CVD or hydrothermal procedures. The effect of solvent on catalytic activity of Sn-MCM-41 materials and leaching tests of impregnated samples were also assessed. Selected materials were characterized by BET, XPS and H2-TPR. The effect of solvent was explained in terms of polarity by the solvatochromic parameter, ET(30), and paraformaldehyde solubility by the Hansen solubility parameter (HSP). Nopol selectivity was enhanced at intermediate values of ET(30), and the highest b-pinene conversion was obtained when the HSP was close to 18.2 MPa0.5. Leaching experiments confirmed that the reaction was truly heterogeneous. Catalysts characterization suggested that tin was deposited as tin oxide nanoparticles, when MCM-41 was modified by CVD and impregnation with stannic and stannous chloride, respectively. Conversely, most of the tin hydrothermally incorporated is presumably present as aggregates in the inner walls of MCM-41 and a small fraction of tin isomorphously substituted silicon atoms.